Disseminated toxoplasmosis in a patient with advanced acquired immunodeficiency syndrome - Ricardo Garcia Pastorello; Anderson da Costa Lino Costa; Marcio Valente Yamada Sawamura; Antonio Carlos Nicodemo; Amaro Nunes Duarte-Neto (University of São Paulo, 2018)
Extracerebral toxoplasmosis, with pulmonary involvement and shock, is a rare form of toxoplasmosis in patients with advanced AIDS. It can mimic pneumocystosis, histoplasmosis, and disseminated tuberculosis, and should be considered in the differential diagnosis of causes of respiratory failure and fulminant disease in this group of individuals, especially in areas where the Toxoplasma gondii infection is highly prevalent and in those without proper use of antimicrobial prophylaxis. We report the case of a 46-year-old male patient who presented to the emergency department with uremia, requiring urgent dialysis. During the laboratorial investigation, the patient had confirmed HIV infection, with a low CD4+ peripheral T-cell count (74 cells/µL). During hospitalization, the patient presented drug-induced hepatitis due to trimethoprim/sulfamethoxazole in a prophylactic dose, requiring interruption of this medication. On the 55th day of hospitalization, the patient developed refractory shock and died. At the autopsy, disseminated toxoplasmosis with encephalitis and severe necrotizing pneumonia were diagnosed, with numerous tachyzoites in the areas of pulmonary necrosis.